BAM FORM 6 – MATRICES

Share this post on:

SOLUTION

1. a)  A = edu.uptymez.com   B = edu.uptymez.com      

                        A + B

                 edu.uptymez.com + edu.uptymez.com

              = edu.uptymez.com = edu.uptymez.com
A + B = edu.uptymez.com

edu.uptymez.com
     For singular matrix,  edu.uptymez.com= 0


edu.uptymez.com
= 2 (8) – k (k) = 0

                    16 = k2 = 0

                    16 = k2

                 edu.uptymez.com = edu.uptymez.com

                      4 = k

                        edu.uptymez.comk = 4

            c) B = edu.uptymez.com

      edu.uptymez.com

            edu.uptymez.com = 2 (-1) – 4 (1)

                        = -2 – 4

                       edu.uptymez.com = -6
edu.uptymez.com

          edu.uptymez.com

           d)  By using inverse method required to solve for x and y
x + 2y = 10

               2x – y = 5

             edu.uptymez.com edu.uptymez.com = edu.uptymez.com

            A = edu.uptymez.com

            edu.uptymez.com = 1 (-1) – 2 (2) = -1 – 4 – 5

            A-1 = 1/ edu.uptymez.com edu.uptymez.com

          A-1  = 1/-5 edu.uptymez.com
edu.uptymez.com


edu.uptymez.com

       edu.uptymez.com

              edu.uptymez.com = edu.uptymez.com

2.   3x – y + 2z = 2

       x – 5y + 2z = 6

      2x + 3y + z = 0

            i) By determinant

           edu.uptymez.com edu.uptymez.com = edu.uptymez.com

      edu.uptymez.com
edu.uptymez.com = 3 edu.uptymez.com – 1 edu.uptymez.com + 2 edu.uptymez.com

                        = 3 (5 – 6) – -1 (1 – 4) + 2 (3 – 10)

                        = 3 (1) + 1 (-3) + 2 (7)

                        = -3 + -3 + -4 = -20

            B = edu.uptymez.com

            edu.uptymez.com= 2 edu.uptymez.com – 1 edu.uptymez.com + 2 edu.uptymez.com

                        = 2 (5 – 6) + 1 (6 – 0) + 2 (18 – 0)

                        = 2 (1) + 1 (6) + 2 (18)

                        = -2 + 6 + 36 = 40

            C = edu.uptymez.com

            edu.uptymez.com = 3 edu.uptymez.com – 2 edu.uptymez.com + 2 edu.uptymez.com

                        = 3 (6 – 0) – 2 (1 – 4) + 2 (0 – 12)

                        = 3 (6) – 2 (3) + 2 (12)

                        = 18 – 6 + -24 = -12

             D = edu.uptymez.com
edu.uptymez.com


= 3 (0 – 18) + 1 (0 – 12) + 2 (3 – 10)

                        = 3 (18) + -1 (12) + 2 (7)

         edu.uptymez.com

edu.uptymez.com

             ii) By inverse

                         edu.uptymez.com edu.uptymez.com = edu.uptymez.com

                        edu.uptymez.com = 3 edu.uptymez.com – 1 1edu.uptymez.com + 2 edu.uptymez.com

                                    = 3 (5 – 6) + 1 (1 – 4) + 2 (3 – 10)

                                    = 3 (-1) + 1 (-3) + 2 (-7)

                                    = -3 + 3 + -14 = -20

                        A = edu.uptymez.com

            Cof 3: + 1 edu.uptymez.com                  cof -1: 1 edu.uptymez.com

                        = + 1 (5 – 6)                          = – 1 (1 – 4)

                        = -1                                         = 3

            Cof 2: + 1 edu.uptymez.com             cof: – 1 edu.uptymez.com

                        = + 1 (3 – 10)                        = -1 (5 – 6)

                        = -7                                         = 1

            Cof 2: + 1 edu.uptymez.com                  cof2: -1 edu.uptymez.com

                        = + 1 (3 – 4)                          = -1 (9 – 2)

                        = -1                                         = -7

            Cof 4 + 1edu.uptymez.com              cof 3: -1 edu.uptymez.com

                        = + 1 (-2 – 10)                      = -1 (6 – 2)

                        = -12                                       = -4

            Cof 1: + 1edu.uptymez.com

                        = + 1 (15 + 1)

                        = 16

   Matrix of the Co factors
             C =  edu.uptymez.com

            Adj A =  edu.uptymez.com

            Inverse A
edu.uptymez.com

edu.uptymez.com

edu.uptymez.com
= edu.uptymez.com

                          = edu.uptymez.com

edu.uptymez.com

 3.    a) 2x + y = 8

               4x – y = 10

            i) Determinant

edu.uptymez.com

             edu.uptymez.com = 2 (-1) – 4 (1)

                  = -2 – 4 = -6

            edu.uptymez.com= edu.uptymez.com

            edu.uptymez.com = 8 (-1) – 10 (1)

                  = -8 – 10 = -18

            edu.uptymez.com = edu.uptymez.com

            edu.uptymez.com = 2 (10) – 4(8)

                  = 20 – 32 = -12

edu.uptymez.com

edu.uptymez.com                    X = edu.uptymez.com
                                   edu.uptymez.com                                                                                                                         

ii) By inverse

                        A = edu.uptymez.com

                        edu.uptymez.com = 2 (1) – 4 (1)

                          = -12 – 4 = -6

edu.uptymez.com
edu.uptymez.com

edu.uptymez.com

                           edu.uptymez.com = edu.uptymez.com

  b) If A=edu.uptymez.com, B = edu.uptymez.com     and C = edu.uptymez.com,   Show that A + B – 2C is singular

            edu.uptymez.com + edu.uptymez.com – 2 edu.uptymez.com

            = edu.uptymez.com – edu.uptymez.com

            = edu.uptymez.comedu.uptymez.com

            = edu.uptymez.com

            = edu.uptymez.com


edu.uptymez.com

  c)  x + y + z = 6

       3x – 2y – z = -1

       2x + 4y + 3z = 19

            i) Determinant
edu.uptymez.com

                        edu.uptymez.com edu.uptymez.com = edu.uptymez.com

            edu.uptymez.com= 1 edu.uptymez.com – 1 edu.uptymez.com + 1 edu.uptymez.com

                        = 1 (-6 + 4) – 1 (9 + 2) + 1 (12 + 4)

                                    = -2 – 11 + 16 = 3

B = edu.uptymez.com

 edu.uptymez.com = 6 edu.uptymez.com – 1edu.uptymez.com + 1edu.uptymez.com

                        = 6 (-6 + 4) – 1 (-3 + 19) + 1 (-4 + 38)

                        = 6 (-2) – 1 (16) + 1 (34)

                        = -12 – 16 + 34 = 6

            C =edu.uptymez.com

            edu.uptymez.com = 1edu.uptymez.com – 6 edu.uptymez.com + 1edu.uptymez.com

                        = 1 (-3 + 19) – 6 (9 + 2) + 1 (57 + 2)

                        = 16 – 6 (11) + 1 (59)

                        = 16 – 66 + 59 = 9

            D = edu.uptymez.com

            edu.uptymez.com = 1edu.uptymez.com – 1 edu.uptymez.com + 6 edu.uptymez.com

                        = 1 (-38 + 9) – 1 (57 + 2) + 6 (12 + 9)

                        = 1 (-34) – 1 (59) + 6 (16)

                        = -34 – 59 + 96 = 3

edu.uptymez.com

                         edu.uptymez.com = edu.uptymez.com


ii) By inverse

            A = edu.uptymez.com edu.uptymez.com = edu.uptymez.com

            edu.uptymez.com = 1 edu.uptymez.com – 1 edu.uptymez.com + 1 edu.uptymez.com     

                        = 1 (-6 + 4) – 1 (9 + 2) + 1 (12 + 4)

                        = 1 (-2) – 1 (11) + 1 (16)

                        = -2 – 11 + 16 = 3

                        edu.uptymez.com

            Cof 1: + 1 edu.uptymez.com                  cof1: + 1 edu.uptymez.com

                        = + 1 (-6 + 4)                            = -1 (9 + 2)

                         = -2                                           = -11

            Cof1: + 1 edu.uptymez.com                      cof 3: -1 edu.uptymez.com

                        = + 1 (12 + 4)                        = -1 (3 – 4)

                        = 16                                     = -1

            Cof2: + 1edu.uptymez.com                         cof1: –      edu.uptymez.com

                        = + 1 (3 – 2)                          = – 1 (4 – 2)

                        = 1                                                      = -2

            Cof2: + 1 edu.uptymez.com                     cof 4: – 1 edu.uptymez.com

                        = + 1 (-1 + 2)                                    = -1 (-1 – 3)

                        = + 1                                                   = 4

            Cof 3: + 1 edu.uptymez.com

                        = + 1 (-2 – 3)

                        = -5

            Matrix cofactors

                     A = edu.uptymez.com

                Adj A = edu.uptymez.com

                        A-1 = 1/ edu.uptymez.com Adj A

                      A-1   = 1/3 edu.uptymez.com

edu.uptymez.com
edu.uptymez.com

                                 edu.uptymez.com

                                 ∴  edu.uptymez.com edu.uptymez.com

7.   a)    A = edu.uptymez.com    B = edu.uptymez.com


Calculate  i) AB

             edu.uptymez.com  x  edu.uptymez.com

          =  edu.uptymez.com

           = edu.uptymez.com

            =  edu.uptymez.com


ii) BA

       A = edu.uptymez.com     B = edu.uptymez.com

        edu.uptymez.com    edu.uptymez.com

     = edu.uptymez.com

     = edu.uptymez.com

    = edu.uptymez.com

b) Find the value of x, y, w and z

            3 edu.uptymez.com = edu.uptymez.com + edu.uptymez.com
            edu.uptymez.com = edu.uptymez.com
                        3x – x = 4

                    2x = 4
2      2
x = 2

                  3y – y = 6 + 2
2y = 6 + 2
2y =8
y = 4

                   3w = 2w + 3
                   3w – 2w = 3
                  w = 3
                    3z = -1 + z + w
                  3z – z = -1 + 3
                   2z = 2
2     2         

                  z = 1

            ∴  x = 2, y = 4, z = 1, w = 3

5.  A transformation is given by the matrix M where M =  edu.uptymez.com    

            Find the (a) image of (-2, 5) under M (b) Inverse of M

              edu.uptymez.com
b)  M = edu.uptymez.com

              edu.uptymez.com = 4 (3) – 2

                     = 12 – 2 = 10

              M-1 = 1/10 edu.uptymez.com

               M-1 = edu.uptymez.com

6. a) If T is linear transformation such that T = edu.uptymez.com and T (x, y)

            (3y, 5x)

            Find T hence evaluate T (1, 2)

            Solution

            edu.uptymez.com edu.uptymez.com = edu.uptymez.com

            edu.uptymez.com = edu.uptymez.com

            ax + by = 3y 

               a =0

              b = 3

            cx + dy = 5x

            c = 5

            d = 0

            T = edu.uptymez.com

            T (x, y) = (3y, 5x)

            T (1, 2) = (6, 5)

            OR

            edu.uptymez.com edu.uptymez.com

            = edu.uptymez.com = edu.uptymez.com

Share this post on: